Modified Inertial Hybrid and Shrinking Projection Algorithms for Solving Fixed Point Problems - Bing Tan; Shanshan Xu; Songxiao Li (Mathematics, 2020)
In this paper, we introduce two modified inertial hybrid and shrinking projection algorithms for solving fixed point problems by combining the modified inertial Mann algorithm with the projection algorithm. We establish strong convergence theorems under certain suitable conditions. Finally, our algorithms are applied to convex feasibility problem, variational inequality problem, and location theory. The algorithms and results presented in this paper can summarize and unify corresponding results previously known in this field.